Vision Loss and Recovery after Baerveldt Aqueous Tube Shunt Implantation. (18th January 2017) - Kim, Esther Lee; Tran, Jeffrey; Töteberg-Harms, Marc; Chahal, Jasdeep; Rhee, Douglas; Chopra, Vikas; Francis, Brian
Abstract : This study aims to determine the course of vision loss after Baerveldt aqueous tube shunt placement and identify risk factors associated with unexplained severe long-term vision loss, or snuff-out. We retrospectively reviewed 247 eyes of 222 patients who underwent Baerveldt implantations at one of two academic institutions. Postoperative vision loss at 6 months following surgery was categorized as mild-to-moderate versus severe and long-term versus transient. Long-term vision loss, defined as 3 or more lines of Snellen visual acuity (VA) loss compared with preoperative VA, occurred in 63 of 247 eyes (25.5%), and 39 had mild-to-moderate and 24 had severe loss. Of these 63 eyes, 18 had no identifiable cause of vision loss. On multivariate analysis, poorer Snellen VA on postoperative day 1 (POD1) was found to be a significant risk factor for long-term vision loss (p = 0.005 ). In addition, the negative change in preoperative versus POD1 Snellen VA (p = 0.021 ) and the presence of split fixation involving the inferonasal quadrant on preoperative Humphrey visual field (p = 0.044 ) were significant risk factors for snuff-out. Transient vision loss occurred in 76 of 242 eyes (30.8%). In conclusion, vision loss is not uncommon after Baerveldt surgery, with snuff-out occurring in 2.4% of cases in this study.